Migration als Wirtschaftsmodell: Die remittances in El Salvador - Rupp, Helen (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
The money sent back by Salvadoran migrants in the Unites States to family and community members staying behind in El Salvador is one of the most obvious aspects of the transnationalisation of Salvadoran society during the last years. The constantly rising remittance flows are not only the sustain of a growing share of Salvadoran households but also keep at flow the national economy. The implementation of an economic model based on the exportation of workforce can explain why the government’s policies rather encourage international migration and the sending of remittances than to fight the reasons behind this mass exodus.